Review of Twenty Years of Ecosystem Services Research at Henfaes Silvopastoral National Network Experiment - Nworji, Michael Jide (Journal of Agricultural Policy, 2020)
Purpose: This study systematically reviewed and synthesised all the scientific literature that has so far been conducted on the ecosystem services of the UK's Silvopastoral National Network Experiment, the Henfaes Silvopastoral Systems Experimental Farm of Bangor University, Wales, and other studies in temperate Europe from 1988 to 2012 to establish what has been done to date, the benefits and contributions to our knowledge base, and potential knowledge gaps and priorities for future research. Methodology: All available papers and grey literatures, since the inception of the UK's Silvopastoral National Network Experiment in 1988, were extracted and reviewed primarily by accessing various electronic databases and existing library collections. The research papers were split into peer-reviewed (published) and non-peer-reviewed (unpublished) papers. The ecosystem services framework was used to relate the four major categories of ecosystem services (provisioning, regulating, cultural and supporting) to the scientific domain of the research studies. The scientific domains addressed include timber or wood-fuel potential, pasture/livestock management, carbon sequestration, soil improvement, water management, and biodiversity enhancement. Findings: Results show that 66 research studies were conducted over the 20-year study period on ecosystem services of which 45% were produced based on studies at Henfaes Silvopastoral Systems Experimental Farm, 32% at UK's Silvopastoral National Network Experiment, 12% were from other silvopastoral systems trials in the UK, and 11% were from European-wide silvopastoral systems studies. The trendline indicated that the number of annual studies on ecosystem services were greatest in the mid and late 1990s than in any other time over the 20-year study period. The studied ecosystem services dealt with provisioning services (40%), regulating services (13%), and supporting services (47%). The scientific domains addressed include timber or wood-fuel potential (20%), pasture/livestock management (20%), biodiversity (20%), carbon sequestration (13%), water management (15%), and soils (12%). Unique contribution to theory, practice and policy: It is hoped that the results of this study will lead to better understanding of the economic and environmental implications of silvopastoral system, and hence generate more attention towards accelerating its adoption and institutionalization in national rural development policies.